Effectiveness of Using Imitation Technique Through English Video Towards Students’ English Pronunciation Ability - Khaliatun Mardiyah; Ana Santika (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study was to find out whether learning English using imitation video technique can improve the English pronunciation ability of class X high school students who were divided into 2 groups, namely the experimental group and the control group. This study used a samples of 50 students taken from 25 students the experimental class and 25 students from the control class. In this study, the researcher used student records to determine the pre-test and post-test. Furthermore, the results of the two tests were tested statistically using the normality test, homogeneity test, and t-test. The average value in the data shows that the pre-test value in the class that received treatment was 46.24 and the average value in the post-test was 72.88. after being applied to imitate English videos, there was an increase in the average score of students by 26.64. then the results of the t-test showed to t-table with a significant level of 5% was 2.93 and the degrees of freedom (df) were 48, for the t-test score was 3.61. As the t-test value is greater than the t-table value, Ho is rejected and Ha is accepted. In measuring the level of effect size with d= 1.78 this shows that this study has strong effective in improving students; English pronunciation skills. Therefore, to improve English pronunciation skills, it is highly recommended to use the technique of imitating English videos through YouTube media.